2005
DOI: 10.1136/oem.2005.020537
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged standing at work and hospitalisation due to varicose veins: a 12 year prospective study of the Danish population: Table 1

Abstract: Background: Recent studies suggest that prolonged standing at work is associated with the development of diseases of varicose veins (VV). Aims: To assess the risk of hospitalisation due to VV in the lower extremities prospectively in workers standing or walking at least 75% of their time at work. Methods: A representative random sample of 9653 working age adults was drawn from the Central Population Register of Denmark in 1991. Of these, 8664 accepted to be interviewed by telephone (response rate 90%). Respond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 13 publications
3
80
0
7
Order By: Relevance
“…Interpretation of this finding is difficult because diseases of the circulatory system include a large range of diagnoses from rather benign ones such as varicose veins to serious, even lifethreatening, diseases such as coronary heart disease. Prolonged standing at work (which is very common for nurses) has been found to be a risk factor for hospital treatment due to varicose veins [35]. One possible explanation could be that nurses who treat these problems overall take better care of themselves and may have lower levels of other risk factors relevant to unemployment.…”
Section: Discussionmentioning
confidence: 97%
“…Interpretation of this finding is difficult because diseases of the circulatory system include a large range of diagnoses from rather benign ones such as varicose veins to serious, even lifethreatening, diseases such as coronary heart disease. Prolonged standing at work (which is very common for nurses) has been found to be a risk factor for hospital treatment due to varicose veins [35]. One possible explanation could be that nurses who treat these problems overall take better care of themselves and may have lower levels of other risk factors relevant to unemployment.…”
Section: Discussionmentioning
confidence: 97%
“…Prolonged standing or walking due to occupational exposure has been suggested to be a cause of VV [2,11,12] . In a longitudinal study with a large sample size in Denmark, workers who stood or walked for 6-7.3 h had a significantly higher risk of surgery of VV than workers who stood or worked for less than 4 h (adjusted hazard ratio 3.17 in men and 2.34 in women) [2] .…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that an outward plasma fluid shift leading to transient interstitial oedema of the lower limbs can lead to acute venous insufficiency (Flore et al, 2004;Novak et al, 1998;van Lieshout et al, 2001). Tuchsen et al (2005) have shown that prolonged standing is associated with varicose veins in a working population.…”
Section: Regulation Of Blood Pressure and Heart Ratementioning
confidence: 97%
“…Prolonged standing at work has been associated with a variety of adverse effects (McCulloch, 2002), such as lower extremity discomfort (Messing et al, 2006), varicose veins (Tuchsen et al, 2005), chronic venous insufficiency (Krijnen et al, 1997a, b) and progression of carotid artery disease (Krause et al, 2000). However, the precise mechanisms linking different standing postures to health effects are not known.…”
Section: Introductionmentioning
confidence: 97%